Odontogenic sinusitis maxillaris: A retrospective study of 121 cases with surgical intervention. Issue 4 (April 2017) - Zirk, Matthias; Dreiseidler, Timo; Pohl, Matthias; Rothamel, Daniel; Buller, Johannes; Peters, Franziska; Zöller, Joachim E.; Kreppel, Matthias
Abstract: Purpose: Otolaryngologists, dentists and maxilla-facial surgeons see patients suffering from odontogenic maxillary sinusitis on a daily routine. The study was performed to investigate the different origins of the odontogenic maxillary sinusitis ranging from periodontitis to augmentative implant surgery. Furthermore, the microbial flora of purulent odontogenic maxillary sinusitis was analyzed in order to present a proper antibiotic treatment in addition to a surgical approach. Materials and methods: A retrospective study was performed, analyzing the clinical trials of 121 patients suffering from odontogenic maxillary sinusitis who undergone surgery. Harvested bacteria were tested for susceptibility on a routine base, surgical reports of removed foreign material or dental focus were reviewed as well as preoperative CBCT. Results: Patients mean age was 56.62 (±16 SD) with a slight female gender dominance. Allergic profile to β-lactam antibiotics had no influence on patients' length of in-hospital stay. 69 out of 121 cases of OMS occurred after dental surgery (extractions, augmentation or implant surgery). Maxillary molars were the teeth mostly hold accountable for an onset without surgery in recent history. 22.3% of the patients possessed a dislocated foreign body in the maxillary sinus. Pseudomonas aeruginosa infection was significantly associated with misplaced foreign bodies (root filling, augmentative dental material e.g. p < 0.05). We protocoled an anaerobic dominance with 45 anaerobes versus 19 aerobes. Ampicillin/Sulbactam (80%) and Piperacillin/Tazobactam (93.3%) present sufficient susceptibly rates to the harvested bacteria. Likewise showed Moxifloxacin (86.3%) equal results, whereas Clindamycin had a poor outcome with merely 50% of the tested bacteria being susceptible to Clindamycin. Conclusion: If OMS is diagnosed dental focus should be treated, misplaced bodies should be removed and purulent exacerbation has to be additionally treated with a calculated antibiotic therapy according to the pathogens resistance patterns.